Fear in Ancient Greek Warfare and its conceptualization in the sources. An introduction (De Rebus Antiquis, 2020)
Fear is commonly regarded as a natural emotion in war, present as wellin ancient Greek warfare. Greek literary sources occasionally emphasize theemotions connected to the contemporary experience of combat from a primarilynarrative perspective. This paper will offer an introduction to the Greek notionand conceptualization of fear in the classical period and its relationship with war,intending to achieve a better understanding of its role in the literary sources and,ultimately, its relevance in Greek culture and warfare.
Keywords: Greek warfare; emotions; fear; cognitive process